Super-sticky Wechat and Chinese society - Chen, Yujie; Mao, Zhifei; Qiu, Jack Linchuan, 1973- (Emerald Publishing Limited, 2018)
App designers dream of creating a platform that users never want to leave, that keeps them glued forever - a platform that is "sticky".Over 846 million WeChat users leave text and voice messages, share life moments, play games, use stickers, purchase rail and flight tickets, shop online, pay utilities and bills, transfer money to friends, and even donate to charity without leaving WeChat, the super-sticky platform. The Economist called WeChat "one app to rule them all", and as it starts to gain global appeal, it is rewriting the rules for social media platforms.This book provides a balanced and nuanced study of how the super-sticky WeChat platform interweaves into the fabric of Chinese social, cultural, and political life. It keeps the wider global and national social media landscape in view and compares and contrasts WeChat with Weibo and QQ, two other popular social media platforms in China, and other Western social media platforms.
Includes index.
Keywords: Online social networks -- China.; Wechat (Firm); Language Arts & Disciplines, Communication Studies.; Communication studies.; elektronické knihy; electronic books